Hexamethyldisilazane-iodine induced intramolecular dehydrative cyclization of diamides: a general access to natural and unnatural quinazolinones - Kshirsagar, Umesh A.; Mhaske, Santosh B.; N. P. Argade (Tetrahedron Letters, 2007)
A simple and efficient general approach to various quinazolinone scaffolds, including peptidomimetic examples, has been demonstrated by employing HMDS/I-2 for the intramolecular dehydrative cyclization of diamides. The protecting groups -Boc, -Fmoc and -Cbz tolerated the present reaction conditions and we did not observe any racemization. The present protocol has also been used as a key step for the efficient four-step syntheses of the naturally occurring quinazolinones, sclerotigenin, (-)-circumdatin-F and (-)-fumiquinazoline-F. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: diamides; HMDS/I-2; intramolecular dehydrative cyclizations; natural and unnatural quinazolinones; synthesis

Facile approach to diverse range of 1,3-diaza-heterocycles: angular/linear selectivity paradigm and a remarkable intramolecular methyl migration - Kshirsagar, Umesh A.; N. P. Argade (Tetrahedron, 2009)
Starting from cyclic anhydrides and tert-butyl 2-aminobenzylcarbamate, simple and efficient synthesis of diverse range of kinetically controlled angular and thermodynamically controlled linear tricyclic and tetracyclic 1,3-diaza-heterocycles have been described via the intramolecular cyclizations of the corresponding imides/anilic acid esters. The effect of imide stability on the angular/linear product selectivity has also been described. The kinetically controlled angular products were successfully transformed to the corresponding thermodynamically controlled linear products by refluxing in methanol or methanol and acetic acid mixture. An interesting in situ 1,2-intramolecular methyl group migration has also been described. (C) 2009 Elsevier Ltd. All rights reserved.

Copper-catalyzed intramolecular N-arylation of quinazolinones: facile convergent approach to (-)-circumdatins H and J - Kshirsagar, Umesh A.; N. P. Argade (Organic Letters, 2010)
A copper-catalyzed intramolecular N-arylation of a quinazolinone nucleus that furnished the central benzodiazepine core unit has been demonstrated to accomplish an efficient convergent total synthesis of (-)-circumdatins H and J.

Total synthesis of proposed auranthine - Kshirsagar, Umesh A.; Puranik, Vedavati G.; N. P. Argade (Journal of Organic Chemistry, 2010)
Starting from CBz-protected glutamic anhydride and Boc-protected o-aminobenzyl amine, the first total synthesis of proposed structure of auranthine has been reported. An intramolecular aza-Wittig reaction involving a lactam carbonyl group that delivered the diazepine core unit was the key step in the synthesis.

Regioselective monoalkylation of dimethyl alkylidenesuccinates: simple approach to dialkyl-substituted maleic anhydrides including chaetomellic acid A - Kshirsagar, Umesh A.; N. P. Argade (Synthesis-Stuttgart, 2011)
Natural and nonnatural dialkylmaleic anhydrides were readily prepared from dimethyl alkylidenesuccinates by sodium hexamethyldisilazide-induced selective monoalkylation followed by base-catalyzed hydrolysis.
Keywords: alkylations; Esters; furans; heterocycles; maleic anhydrides

Eosin Y photoredox catalyzed net redox neutral reaction for regiospecific annulation to 3-sulfonylindoles via anion oxidation of sodium sulfinate salts - Rohokale, Rajendra S.; Tambe, Shrikant D.; Kshirsagar, Umesh A. (Organic & Biomolecular Chemistry, 2018)
An eosin Y photoredox catalyzed net redox neutral process for 3-sulfonylindoles via the anionic oxidation of sodium sulfinate salts and its radical cascade cyclization with 2-alkynyl-azidoarenes was developed with visible light as a mediator. The reaction offers metal and oxidant/reductant free, visible light mediated vicinal sulfonamination of alkynes to 2-aryl/alkyl-3-sulfonylindoles and proceeds via the generation of a sulfur-centered radical through direct oxidation of the sulfinate anion by an excited photocatalyst with a reductive quenching cycle. The mild conditions, use of an organic dye as photo-catalyst, bench stability and easily accessible starting materials make the present approach green and attractive.

Metal-free synthesis of 3-thiocyanatobenzothiophenes by eosin Y photoredox-catalyzed cascade radical annulation of 2-alkynylthioanisoles - Tambe, Shrikant D.; Jadhav, Mahesh S.; Rohokale, Rajendra S.; Kshirsagar, Umesh A. (European Journal of Organic Chemistry, 2018)
A convenient, efficient, metal-free synthesis of 3-thiocyanatobenzothiophenes has been developed that uses eosin Y in a visible-light-mediated photoredox-catalyzed anion oxidation of the ammonium salt of thiocyanate and proceeds through the cascade radical annulation of 2-alkynylthioanisole at room temperature. The present protocol requires visible light as a green energy source, an organic dye as the photocatalyst, and oxygen as a green oxidant to provide a mild route with a broad substrate scope for the formation of potentially bioactive 3-substituted benzothiophene derivatives in good yields.

Visible-light-mediated eosin Y photoredox-catalyzed vicinal thioamination of alkynes: radical cascade annulation strategy for 2-substituted-3-sulfenylindoles - Tambe, Shrikant D.; Rohokale, Rajendra S.; Kshirsagar, Umesh A. (European Journal of Organic Chemistry, 2018)
An organic dye photoredox-catalyzed regiospecific radical cascade annulation strategy of 2-alkynyl-azidoarenes to generate 3-sulfenylindoles via vicinal thioamination of alkynes at room temperature, mediated by visible light, was developed. The method requires mild conditions, including visible light as a traceless green energy source, room temperature, eosin Y organic dye as a photoredox catalyst, ambient air as oxidant, and easily available starting materials to provide a green, efficient, metal- and strong-oxidant-free synthesis of 3-sulfenylindoles with broad substrate scope through vicinal thioamination of alkynes.